Error Detection and Correction to Enhance the Data Rate of Smart Metering Systems Using Modbus-Rtu - Urrea-Onate, E; Kern-Molina, J; Morales-Diaz, C (Springer Science and Business Media Deutschland GmbH, 2021)
This work presents a system and method to improve transmission quality in smart meter networks that use Modbus-RTU. Energy management systems in industries, buildings and urban infrastructure use smart meters interconnected in a network. These systems can demand a great quantity of interconnected devices, which sets down increasing requirements to communication networks in terms of transmission quality and speed. At the plant level, Modbus-RTU is the de facto protocol for the interconnection of electric meters. However, since it was created more than 4 decades ago, this protocol imposes constraints to transmission speed, maximum number of interconnected devices and error detection mechanisms. This proposal is applicable to Modbus-RTU meter networks that need to increase data transmission speed to be integrated into smart metering systems but face problems due to the increase in transmission errors caused by noise and electromagnetic interference in the field bus. The effectiveness of the proposed method to increase the data rate while maintaining reliability is studied, and simulation and experimental results are presented. © 2020, Springer-Verlag GmbH Germany, part of Springer Nature.